IoT Based Monitoring and Control System using Sensors - S, Madhura; G, Deepthi; B, Chihnitha; D, Disha (Journal of ISMAC, 2021)
Various physical parameters like humidity, temperature, raindrop, GSM, atmospheric pressure and LDR can be monitored effectively and can be made more interactive with the help of different sensors that are interfaced with microcontrollers like ATmega328P. All the sensors can be connected to this microcontroller ATmega328P as the center preparing unit for the whole framework and plans can be associated with the microcontroller. The real-time monitoring of the various systems becomes possible with this IoT based system. The Paper displays different application based on IoT and proves that the monitoring and control of the system becomes flexible, robust and effective for any real-time implementation .